The Influence of Digital Media on Students’ Sports Behavior and Psychology - Jingjing Chen; Lin Lin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
To explore the impact of digital media on students' sports behavior and psychology. This article adopts methods of literature review, questionnaire survey, interview, mathematical statistics, and logical analysis to investigate the current situation of sports culture dissemination methods on high school students' sports attitudes and behaviors, as well as the main transmission factors that affect college students' sports attitudes and behaviors. A survey was conducted on 1000 college students and 20 sports teachers from four universities in a certain province, and the psychological health characteristics of high school students under the conditions of sports behavior attitudes were analyzed, based on this, corresponding suggestions and countermeasures were proposed. The results indicate that the dissemination of sports culture will have an impact on college students' sports attitudes and behaviors, and different dissemination methods will also have different impacts on students; Due to the different physiological and psychological characteristics of college students of different genders, there are differences in their cognition, attitude, habits, and other aspects of sports. Therefore, the sports attitudes and behaviors of male and female students are also influenced differently by the dissemination of sports culture; Print media, audiovisual media, interpersonal communication, and environmental factors all have an impact on college students' sports attitudes and behaviors. The level of physical exercise and physical exercise behavior have a significant impact on indicators such as somatization, compulsion, interpersonal relationships, depression, and anxiety. Conclusion: The dissemination of sports culture will have an impact on college students' sports attitudes and behaviors, and different dissemination methods will also have different impacts on students; The level of physical exercise and physical exercise behavior have a significant impact on indicators such as somatization, compulsion, interpersonal relationships, depression, and anxiety.